2016
DOI: 10.3329/bjp.v11is1.26419
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of flavonoids from onion skins and their effects on K562 cell viability

Abstract: To investigate the anti-proliferative activity of flavonoids from onion skins, extraction by 50% ethanol (v/v), soxhlet polar fractionation, pH gradient separation, thin-layer chromatography, and recrystallization methods were used to isolate and purify flavonoids from dry onion skins. Anti-proliferative activities of some flavonoids obtained on leukemia K562 cell line were deter-mined by MTT assay. Results showed that flavonoids of onion skins were mainly in form of quercetin, kaempferol, isorhamnetin, apigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“….00 (d) (C-5''), 61.14 (t) (C-6''). These data were found to be consistent with those reported in the literature for 3-O-β-D-glucopyranoside (Shi et al, 2016;Islam et al, 2012 andLi et al, 2008), and compound 3 identified as 3-O-β-D-glucopyranoside.…”
Section: Stigmast-4-en-3-one (2)supporting
confidence: 82%
See 1 more Smart Citation
“….00 (d) (C-5''), 61.14 (t) (C-6''). These data were found to be consistent with those reported in the literature for 3-O-β-D-glucopyranoside (Shi et al, 2016;Islam et al, 2012 andLi et al, 2008), and compound 3 identified as 3-O-β-D-glucopyranoside.…”
Section: Stigmast-4-en-3-one (2)supporting
confidence: 82%
“…Compound 3 obtained in the form of yellow powder with a melting point 872.6 °C and completely soluble in methanol, Fluorescent under ultraviolet light at a wavelength 254 and 360 nm, indicated there is founded conjugated double bonds. Comparison of physical data and physicochemical compound3.3-O-β-D-glucopyranoside or Isoquercetin shows a very high suitability (Shi et al, 2016;Islam et al, 2012 andLi et al, 2008), thus compound 3 was identified as 3-O-β-D-glucopyranoside or Isoquercetin.…”
Section: -O-β-d-glucopyranoside (3)mentioning
confidence: 99%
“…MSCs migration ability is an important characteristic of the MSCs, which is not only the foundation of MSCs' autonomous migration to the damaged tissue after intravenous injection, but also the theoretical basis of MSCs intravenous injection treatment of visceral injuries and systemic diseases, such as myocardial infarction [23]. Recent studies indicate that inflammatory chemokine receptors, especially CCR1 and CCR2, are closely related to MSCs migration ability in/during myocardial infarction [24][25][26][27][28]. The expression reduction of MSCs surface migration related receptor and oversize cause a decline or loss of MSCs migration capability, resulting in more than 70% of MSCs obstructed in the lung after intravenous injection and only a very small amount (<5%) of the cells reached the infarct cardiac tissue [29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…There are several types of flavonoids present in the A. cepa in scales and disc of onion bulbs (Wiczkowski et al 2008;Slimestad et al 2007;Rodr ıguez Gald on et al 2008;Ko et al 2011;Shi et al 2016;Rodrigues et al 2017). More than 80% of the total content of flavonoids exists in the outer scales of A. cepa which is a result of exposure to sunlight.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Ashwini and Sathishkumar (2014);Lanzotti (2006),Benmalek et al (2013),Corzo-Mart ınez et al (2007),Yamamoto and Yasuoka (2010),Nile and Park (2014),Rhodes and Price (1996),Wiczkowski et al (2008),Shi et al (2016), Rodr ıguez Gald on et al (2008), Ko et al (2011), Rodrigues et al (2017), Slimestad et al (2007) Organosulfuric compounds Thiosulphinates, cepaenes, cysteine, S-methyl cysteine sulfoxide, diallyl disulphide, allyl methyl sulphide, allyl propyl disulphide, gamma-L-glutamyl-trans-S-1propenyl-L-cysteine sulfoxide, S-propenyl cysteine sulfoxide, S-alk(en)yl cysteine sulfoxides, S-allyl cysteine sulfoxide Ashwini and Sathishkumar (2014), Lanzotti (2006), Nile and Park (2014), Benmalek et al (2013) Allicin Diallyl disulphide, diallyl trisulphide and ajoene Ashwini and Sathishkumarn (2014), Lanzotti (2006), Nile and Park (2014), Corzo-Mart ınez et al (2007), Benmalek et al (2013) Phenolic compounds Phenolics, phenolic acids, anthocyanins and hydroxycinnamic acid Lanzotti (2006), Nile and Park (2014) Lipophilic antioxidants Dialkyl disulphides, aglycones, anthocyanin, saponins and fistulosin (octadecyl 3-hydroxyindole)…”
mentioning
confidence: 99%